Health-Related Lifestyles in Relation to Body Mass Index Among Young and Middle-Aged Women in Japan - Rupa Singh; Carolyn K. Nyamasege; Steven R. Hawks; Yukiko Wagatsuma (Women's Health Reports, 2022)
Background: Being underweight, overweight, or obese can lead to adverse health effects. Hence, it is important to understand the specific factors that change the burden of underweight and overweight to target appropriate disease control strategies. This study was designed to examine the prevalence and factors associated with underweight and overweight among young and middle-aged women in Japan. Materials and Methods: A cross-sectional study was conducted among women aged 20?59 years who participated in health checkups at a regional health care center in 2018 and 2019 (N?=?1722). The assessments included anthropometric, blood pressure measurements, and a standardized self-administered questionnaire. Multivariable logistic regression analysis assessed lifestyle factors associated with body mass index for underweight <18.5?kg/m2) and overweight/obesity (25.0?kg/m2 and above). Results: The prevalence of underweight and overweight/obesity were 12.3%, and 22.5%, respectively. No lifestyle factors were found to be significantly associated with being underweight. Having dinner within 2 hours before bed was positively associated with being overweight/obese [adjusted odds ratio (AOR): 1.448, 95% confidence interval (CI): 1.014?2.068]. Women who gained 10?kg since their 20s were more likely to fall into overweight/obesity category (AOR: 9.674, 95% CI: 1.014?2.068). Women who were using a lipid-lowering medication (AOR: 3.150, CI: 1.892?5.246) were associated with three times higher risk of being overweight/obese. Hypertension and dyslipidemia were significantly associated with overweight/obesity (AOR: 3.094, 95% CI: 2.201?4.351 and AOR: 2.498, 95% CI: 1.831?3.409, respectively). Conclusion: One in five middle-aged women was overweight or obese, whereas one in eight was underweight. In relation to the prevention of overweight/obesity, specific health promotion messages regarding eating timing should be developed.